Covid-19 vaccine acceptance among individuals incarcerated in Connecticut state jails - Margaret L. Lind; Byron S. Kennedy; Murilo Dorion Nieto; Amy J. Houde; Peri Sosensky; Ryan Borg; Derek A. T. Cummings; Albert I. Ko; Robert P. Richeson (BMC, 2023)
Abstract Background Vaccine hesitancy is common among incarcerated populations and, despite vaccination programs, vaccine acceptance within residents remains low, especially within jails. With the goal of assessing the Connecticut DOC's COVID-19 vaccine program within jails we examined if residents of DOC operated jails were more likely to become vaccinated following incarceration than in the community. Specifically, we conducted a retrospective cohort analysis among people who spent at least one night in a DOC-operated jail between February 2 and November 8, 2021, and were eligible for vaccination at the time of incarceration (intake). We compared the vaccination rates before and after incarceration using an age-adjusted survival analysis with a time-varying exposure of incarceration and an outcome of vaccination. Results During the study period, 3,716 people spent at least one night in jail and were eligible for vaccination at intake. Of these residents, 136 were vaccinated prior to incarceration, 2,265 had a recorded vaccine offer, and 479 were vaccinated while incarcerated. The age-adjusted hazard of vaccination following incarceration was significantly higher than prior to incarceration (12.5; 95% Confidence Intervals: 10.2-15.3). Conclusions We found that residents were more likely to become vaccinated in jail than in the community. Though these findings highlight the utility of vaccination programs within jails, the low level of vaccination in this population speaks to the need for additional program development within jails and the community.